Jawapan

2015-11-05T11:36:25+08:00
Let say the question is 3x² +9x -35 = 0

3x² +9x -35 = 0
x² +3x -35/3 = 0
x² +3x = 35/3
x² +3x +(3/2)² = 35/3 +(3/2)²
(x +3/2)² = 35/3 + 9/4
(x +3/2)² = 167/12
x +3/2 = √(167/12)
x +3/2 = +- 3.7305

x +3/2 = 3.7305
x = 3.7305 -3/2
x = 2.2305

x +3/2 = -3.7305
x = -3.7305 -3/2
x = -5.2305
2015-11-05T12:01:51+08:00
Penggunaan rumus
3x² + 9x + 35 = 0
a = 3
b = 9
c = 35
$\begin{align} \ x&= \frac{-b\pm \sqrt{ b^{2} -4ac} }{2a}\\&=\frac{-9\pm \sqrt{ 9^{2} -4(3)(35)} }{2(3)}\\&=\frac{-9\pm \sqrt{ 81 -420} }{6}\\&=\frac{-9\pm \sqrt{ -339} }{6} \end{align}